Azacytidine plus olaparib for relapsed acute myeloid leukaemia, ineligible for intensive chemotherapy, diagnosed with a synchronous malignancy. Issue 13 (16th June 2021) - Iluta, Sabina; Pasca, Sergiu; Gafencu, Grigore; Jurj, Ancuta; Terec, Andreea; Teodorescu, Patric; Selicean, Cristina; Jitaru, Ciprian; Preda, Alexandra; Cenariu, Diana; Constantinescu, Catalin; Iordache, Maria; et al.
Abstract: Patients with relapsed/refractory acute myeloid leukaemia (AML), ineligible for intensive chemotherapy and allogeneic stem cell transplantation, have a dismal prognosis. For such cases, hypomethylating agents are a viable alternative, but with limited success. Combination chemotherapy using a hypomethylating agent plus another drug would potentially bring forward new alternatives. In the present manuscript, we present the cell and molecular background for a clinical scenario of a 44‐year‐old patient, diagnosed with high‐grade serous ovarian carcinoma, diagnosed, and treated with a synchronous AML. Once the ovarian carcinoma relapsed, maintenance treatment with olaparib was initiated. Concomitantly, the bone marrow aspirate showed 30% myeloid blasts, consistent with a relapse of the underlying haematological disease. Azacytidine 75 mg/m 2 treatment was started for seven days. The patient was administered two regimens of azacytidine monotherapy, additional to the olaparib‐based maintenance therapy. After the second treatment, the patient presented with leucocytosis and 94% myeloid blasts on the bone marrow smear. Later, the patient unfortunately died. Following this clinical scenario, we reproduced in vitro the combination chemotherapy of azacytidine plus olaparib, to accurately assess the basic mechanisms of leukaemia progression, and resistance to treatment. Combination chemotherapy with drugs that theoretically target both malignancies might potentially be of use. Still, further research, both pre‐clinical and clinical, is needed to accurately assess such cases.